Evaluation of Ocular Surface Changes Seen in Computer Users - Zeynep Büyükbaş; Mehmet Kemal Gündüz; Banu Bozkurt; Nazmi Zengin (Türk Oftalmoloji Dergisi, 2012)
Pur po se: To evaluate the ocular surface changes related to computer use. Ma te ri al and Met hod: 40 volunteered subjects working in secretarial duties who spend at least 6 hours a day using computers in Selcuk University Meram Faculty of Medicine (Group 1) and 50 healthy control subjects who spend less than 6 hours a day using computers (Group 2) were evaluated. Following routine ophthalmological examination, tear break up time (BUT), Schirmer’s test (with topical anesthesia and without topical anesthesia) and OSDI (Ocular surface disease index) were recorded for all subjects. All computer users were visited at their working environment to evaluate the computers’ monitor properties, monitor positions, and the existence of air conditioner and to count the eye blinks per minute during computer use. Statistical analyses were made by using SPSS software package. Wilcoxon signed-rank test was used in the comparison of right and left eyes, whereas Mann-Whitney U test was used in the comparison of Group 1 with Group 2; p<0.05 was considered statistically significant. Re sults: There were 18 males (45%) and 22 females (55%) with a mean age of 27.73±4.8 years in Group 1. There were 27 males (54%) and 23 females (46%) with an average age of 25.96±4.2 years in Group 2. Time spent on computer use was 9.00±1.8 hours/day in Group 1 and 1.92±1.1 hours/day in Group 2 (p<0.001). Eye blinks per minute, BUT, and Schirmer’s test with/without anesthesia were significantly lower in Group 1 compared to Group 2 (p<0.001), whereas OSDI scores were significantly higher in Group 1(p<0.001). There were no differences in tear parameters between subjects with and without air conditioning in Group 1 (p>0.05). BUT, Schirmer’s test with anesthesia and OSDI scores showed no differences according to monitor position and properties (p>0.05). Dis cus si on: Long-term computer use leads to a decrease in eye blink rate, deterioration in tear function tests and dry eye symptoms. (Turk J Ophthalmol 2012; 42: 190-6